(untitled) (Journal of Renal and Hepatic Disorders, 2021)
To retrospectively evaluate databases for indications and results of “bench surgery technique” in ex vivo or ex situ renal cancer resection as a lost alternative of savage renal function in renal malignancy or benign large tumors. We retrospectively evaluated PUBMED databases, including studies from 1980 to 2020. Only very few studies had analyzed “ex vivo [and] ex situ renal resection, extracorporeal renal resection, [and] renal autotransplantation.” Ex vivo renal resection and autotransplantation is the last chance in patients with renal cancer, but manifests numerous difficulties during and after the surgery. However, we noted that in some patients it provided good control over cancer, prevented long-term dialysis, and avoided renal transplantation, thus giving patients a good quality of life.